Ripple effect on housing prices. Evidence from tourist markets in Alicante, Spain - Taltavull de La Paz, Paloma; López, Enrique; Juárez, Francisco (International Journal of Strategic Property Management, 2017)
This paper analyses the house price diffusion effect in an economic-mixed region where the costal amenities strongly attracts second home and temporal residents while the main region’s city is an administrative centre in alicante province, Spain. The region is called Vega Baja country with 2 well known foreign-Europeans destination areas are located (Orihuela costa and Torrevieja). Using geo-referenced data, the paper explores the ripple effect on house prices between the coastal and inland areas, versus Orihuela capital. To control by heterogeneity and spatial autocorrelation, the model estimates housing prices controlled by quality including 33 house characteristics and spatial autocorrelation applying an SAR-hedonic based model which is estimated yearly for the period 2007–2012. Once controlled by quality, the estimated prices are used to seek 3 evidences of ripple effect: with spatial contiguity (spatial diffusion in the short distance), without special contiguity (long distance) and constant relative prices ratio, using Lagrange Multiplier test and Moran’s I, and Spatially Weighted Two Stage Least Squares (SW2SLS) including spatial lag and errors in the model. Results show the existence of spatial autocorrelation patterns in a well-defined local clusters and highlight evidence of ripple effect between Orihuela city and the coastal and inland areas but with lagged effect.First published online 08 Dec 2016